R.C. Das, evangelical prophet for contextual Christianity - Richard, H. L., 1955-; Christian Institute for the Study of Religion and Society, Bangalore; I.S.P.C.K. (Organization) (Delhi : Published for CISRS, Bangalore, by ISPCK, 1995)
Life and work of R.C. (Rajendra Chandra) Das, 1887-1976, Indian evangelist, and founder of the Khristapanthi Ashram, Varanasi.
Includes bibliographical references.
Keywords: Das, R. C. -- 1887-1976.; Evangelists -- India -- Biography; Christianity and other religions -- Hinduism; Hinduism -- Relations -- Christianity; Christianity -- India